COVID-19 Associated Pulmonary Aspergillosis: A Case Series - Mira Yulianti; Christian Johan; Eric Daniel Tenda; Gurmeet Singh; Herikurniawan Herikurniawan; I Putu Eka Krisnha Wijaya (Interna Publishing, 2022)
Coronavirus disease 2019 (COVID-19) has been a worldwide pandemic with several problems, one of which is the lack of definitive treatment. COVID-19-associated pulmonary aspergillosis (CAPA), the presence of invasive pulmonary aspergillosis (IPA) in COVID-19 patients, is one of the concerning secondary infections associated with higher mortality and worse clinical outcomes. Diagnosing CAPA may be challenging due to the possible absence of classic host factors and clinical symptoms or obscured radiological findings. We described two CAPA cases, which were suspected due to persistent respiratory failure despite standard treatment of COVID-19 with additional therapies and antimicrobial agents for secondary infections, eventually diagnosed with serum galactomannan testing. Clinical conditions of both patients improved significantly after the administration of voriconazole. This case series emphasizes the importance of being aware of clinical suspicions indicating CAPA followed by galactomannan testing as a relatively fast, noninvasive test for its diagnosis, which leads to appropriate antifungal treatment.